RETRACTED: Prosocial behavior in early adulthood: A Big Five Personality Trait analysis - Fauzi, Fikriyah Iftinan; Yunita, Yunita; Langit, Angelia Sekar (INSPIRA: Indonesian Journal of Psychological Research, 2025)
This article has been retracted: please see INSPIRA: Indonesian Journal of Psychological Research Retraction, Withdrawal, & Correction (R-W-C) Policy (https://journal.iainlangsa.ac.id/index.php/inspira/rwc-policy). This article has been retracted at the request of the corresponding author. The corresponding author claimed the article had been submitted to another journal.